Pengembangan Bahan Ajar Dongeng Berbasis Discovery Learning Pembelajaran Bahasa Indonesia di Kelas V SD Negeri 21 Kaur - Dina Marliana; Abdul Muktadir; Puspa Djuwita (Universitas Bengkulu, 2023)
The type of research used is research and development or Research and Development (R&D). The development research model used to modify the 4D model (Four D model). Development with the 4D model consists of four stages, namely the define, design, develop, and disseminate stages. There are two types of data obtained from the development of teaching materials, namely qualitative data and quantitative data. The instruments in this study included documentation, interviews, teacher and student response questionnaire validation sheets. There are two types of data obtained from the development of teaching materials, namely qualitative data and quantitative data. The instruments in this study included documentation, interviews, teacher and student response questionnaire validation sheets. The object of this development research is a teaching material product. While the subjects in this study were experts, teachers and elementary school students 21 Kaur. The feasibility of DL-based teaching materials is in the category of quite feasible or valid (moderate) with an average of 54% based on the results of validation by material experts, namely 53%, validation by language experts, namely 55% and validation by presentation experts, namely 54%. User responses regarding DL-based teaching materials based on the results of small group scale tests showed that DL-based teaching materials in Indonesian language learning fairy tale material for class V 21 Kaur elementary school which were developed were in the very good category with a percentage of teacher responses of 95.50% and the results student responses of 98.30%.